Gender Differences: The Role of Built Environment and Commute in Subjective Well-Being - Chen Gui; Yuze Cao; Fanyuan Yu; Yue Zhou; Chaoying Yin (Buildings)
The literature has shown extensive interest in exploring the factors of subjective well-being (SWB). However, most research has conducted cross-sectional analysis of the built environment (BE), commute, and SWB, and little is known about gender differences in their connections. Based on two periods of survey data of 4297 respondents from China, the study performs a cross-sectional and longitudinal examination of whether the BE and commute have effects on SWB, and how the effects differ between men and women. The results reveal that BE features, including destination accessibility and residential density, significantly affect SWB, with stronger impacts observed among men. Men benefit more from greater accessibility and are more negatively affected by higher residential density than women. In contrast, commute mode and duration influence SWB in similar ways for both genders. A shift from nonactive to active commuting improves well-being for men and women alike. Furthermore, certain life events produce gender-specific effects. For instance, childbirth increases SWB for men but decreases it for women. These findings highlight the importance of gender-sensitive planning in building inclusive urban and transportation environments that enhance population well-being.